Pravni vidiki trajnostnega financiranja - Arzenšek, Urška (Pravni letopis, 2023)
The perception that solely high returns and profits are imperative in financial markets has changed in recent years, with a growing number of investors looking to invest sustainably. As a consequence, financial products are increasingly being advertised as such. In order to prevent the deception of investors about the sustainability of investments (financial greenwashing), the European Union is the first to legislate the area of sustainability reporting of companies and financial products. The paper gives a brief overview of EU legislation and its shortcomings. It then discusses the civil liability of asset managers and listed companies for financial greenwashing, whereby several issues are raised, for instance, impending damage because of sea level rise, relief of liability, and the extent of pecuniary damage. Moreover, the paper concludes that current tort law is based on the traditional concept of pecuniary damage, as non-pecuniary damage cannot be claimed due to the numerus clausus of its forms. Even though investor action for damages because of financial greenwashing is still in its infancy in the West, where tort law is complementary to public and corporate law, more such actions can be expected due to the increased investor activism.
Keywords: Evropska unija; finančni trgi; odškodninska odgovornost; odškodninsko pravo; pravna ureditev; trajnostne finance; trajnostne naložbe; vlagatelji